Аpplication of rotation method for estimating noise stability diversity reception of signals - Vladimir Petrovich Pashintcev; Alexander Fedorovich Chipiga; Mariya Anatolievna Lapina; Oleg Vladimirovich Malsugenov; Ilya Evgenievich Hohlov (Наука. Инновации. Технологии)
The article suggests a method of determination of the eigenvalues of the correlation matrix to assess the diversity of incoherent noise reception using the method of rotations.